The Devils Lake Planning Grant. Final Report - Brady, William J.; Thompson, Irving D.; Devils Lake Public Schools, ND. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
Results of a planning grant received by the Devils Lake, North Dakota, school district under Title III of the Elementary and Secondary Education Act (ESEA) are presented. The project included an enrollment survey of the public and non-public schools in a 10-county area; a vocational survey of seniors, parents of seniors, juniors, and sophomores in local schools; a survey of employers and employees in Ramsey County; and an examination of education at the Fort Totten Indian reservation. Results of the various surveys are presented in tabular form, with brief discussions and recommendations for overcoming deficiencies in the educational program. (TL)
Sponsoring Agency: Division of Plans and Supplementary Centers, BESE.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: American Indians; Community Resources; Curriculum Development; Educational Programs; Employment; Rural Youth; Vocational Education; Educational Quality; Rural Schools; School Districts; Secondary School Students; Surveys; Vocational Interests; North Dakota (Devils Lake); North Dakota